The Impact of Social Media Influencers on BA students: A Study Targeting a Sample Chosen from the Students Enrolled at the University of Jordan: Snapchat as a Model - Atieh, Nesreen Nabil Rawhe; Salahat, Abeer Ali Al-; Arabi, Rakan Ayoub Abu (International Journal of Membrane Science and Technology, 2023)
The present study aimed to explore the impact of social media influencers on the BA students enrolled at the University of Jordan from the perspective of those students. It targets Snapchat as a model. It targets the behavioral and language-related areas. The researcher of the present study adopted a descriptive approach. She developed a questionnaire for meeting the study’s goal. This questionnaire consists from twenty two (22) items. It targets two areas. The first area is represented in the impact of social media influencers on students in language-related aspects. The second area is represented in the impact of social media influencers on students in behavioral aspects. The study’s population is represented in all the female and male BA students who were enrolled at the humanities and scientific faculties at the University of Jordan during the second semester of the academic year 2023 / 2024. It consists from 46114 students. Data was collected online from a random sample consisting from 269 students. It was found that the extent of impact of social media influencers on the BA students in language-related aspects is moderate. It was found that the extent of impact of social media influencers on the BA students in behavioral aspects is low. There isn’t any significant difference between the respondents ‘attitudes which can be attributed to (gender, faculty, academic year, or number of hours spent on using Snapchat) in the language-related aspects. There isn’t any significant difference between the respondents ‘attitudes which can be attributed to (gender, faculty, or academic year) in the behavioral aspects. There is a statistically statistically significant difference – at the statistical significance level of (a = 0.05)- between the respondents ‘attitudes which can be attributed to the number of hours spent on using Snapchat in the behavioral aspects. The latter difference is for the favor of the ones who spent three hours or more. The researcher of the present study offered several recommendations. For instance, she recommends conducting studies to explore the impact of social media on the behavior of adolescents and youth. She recommends using the results of such studies to set strategic plans and developing programs targeting youth.